O morebitnem vplivu pravopisne norme Konstantina Kostenečkega na prizrenski prepis Dušanovega zakonika - Grošelj, Robert (Slavistična revija, 2004)
The author analyzes the orthographic features of the Prizren redaction of Dušan's Code (begining of the 16th c.), which is one of the Serbian monuments of the "Resava" edition. Serbian Cyrillic orthography of the "Resava" type is presumed to be the result of Konstantin Kostenečki's linguistic-normative efforts. Basing his analysis of the writing of individual characters on Kostenečki's principles, the author points out the differences between the orthography of the Prizren redaction of Dušan's Code and the "Resava" monuments on the one hand, and Kostenečki's orthographic principles on the other.
Keywords: Dušanov zakonik; Middle Ages; orthography; pravopis; prepisi; Serbia; Srbija; srednji vek; stara cerkvena slovanščina